Medical students' distress during the transition to the endemic phase of COVID-19 in China: The association with temperament traits and attachment styles - Carmenrita Infortuna; Xiaolin Yang; Ray Wang; Gianluca Pandolfo; Ilona Cazorla; Julian Dupont; Veolette Hanna; Valerie Iosim; Mirai Mikhail; Alex Yu; Stanley R. Terlecky; Florian P. Thomas; et al. (AIMS Public Health)
ObjectiveThe transition of COVID-19 into the endemic phase in China has posed additional challenges to medical student's well-being, and increased the odds of mental distress. Although affective temperament traits and adult attachment styles accompany crisis-induced stress, whether this applies to medical students in the endemic phase has yet to be determined. The aim of present study is to test if temperament traits and adult attachment style can predict stress in Chinese medical students.MethodsMedical students (N = 402) enrolled in the undergraduate medical program at the Southern Medical University, Guangdong, China completed an online survey in May 2022. Most participants were female (62.4%), with a mean age of (21.3 ± 3.1). The individual temperament traits and adult attachment styles were assessed using the Chinese version of the Temperament Evaluation of Memphis, Pisa, Paris, and San Diego-auto-questionnaire short version (TEMPS-A), and the Attachment Style Questionnaire (ASQ).ResultsThe participants showed significant distress as assessed with the K10: 19 (15–24) (median, Q1, Q3). Furthermore, a multiple linear regression analysis indicated that cyclothymic (β = 2.1, p = 0.048) and depressive (β = 1.2, p = 0.001) temperament traits and an insecure attachment (ASQ-anxious: β = 0.19, p = 0.006; ASQ-avoidant: β = 0.07, p < 0.001) predicted pandemic-related distress.ConclusionsDimensions of both affective temperaments and attachment styles were associated with stress in the medical students during the transition to the endemic phase. The investigations of these psychological variables provided new information regarding risk factors for endemic-related distress, and pointed to potential targets for counseling and developing programs to support the medical students' mental health.